The Leverage of Protest: Market, Media, and Reputational Disruption in Social Movement Success. Issue 1 (18th December 2019) - Banerjee, Tarun; Case, Benjamin
Abstract : How do social movements gain concessions from large corporations? The ability of protests to attain leverage by imposing disruption costs on their targets is widely assumed but less often tested. In this article, we assess the ability of protests to attain concessions by disrupting three broad sources of interest to firm officials: maximizing shareholder value, gaining positive media, and fostering a well‐reputed image. In contrast to the body of research on the benefits to movements from shaping media discourses and damaging the reputations of their targets, we find that only market disruption provides protests with leverage. We show this through statistical analyses of an original database of protests against large corporations in the United States over five years, 2005–2009. This study advances social movement and organizational research by demonstrating the ways in which the interests of large corporations provide insurgents with means of attaining leverage over their targets. It also speaks to the broad debate over the importance of disrupting the material versus symbolic interests of movement targets. Our results suggest that when it comes to obtaining concessions from large corporations, it is material disruption and not symbolic disruption that provides movements with leverage.